A priori-defined diet quality indices, biomarkers and risk for type 2 diabetes in five ethnic groups: the Multiethnic Cohort. Issue 4 (6th September 2017) - Jacobs, Simone; Boushey, Carol J.; Franke, Adrian A.; Shvetsov, Yurii B.; Monroe, Kristine R.; Haiman, Christopher A.; Kolonel, Laurence N.; Le Marchand, Loic; Maskarinec, Gertraud
Abstract: Dietary indices have been related to risk for type 2 diabetes (T2D) predominantly in white populations. The present study evaluated this association in the ethnically diverse Multiethnic Cohort and examined four diet quality indices in relation to T2D risk, homoeostatic model assessment-estimated insulin resistance (HOMA-IR) and biomarkers of dyslipidaemia, inflammation and adipokines. The T2D analysis included 166 550 white, African American, Native Hawaiian, Japanese American and Latino participants (9200 incident T2D cases). Dietary intake was assessed at baseline using a quantitative FFQ and T2D status was based on three self-reports and confirmed by administrative data. Biomarkers were assessed about 10 years later in a biomarker subcohort ( n 10 060). Sex- and ethnicity-specific hazard ratios were calculated for the Healthy Eating Index-2010 (HEI-2010), the alternative HEI-2010 (AHEI-2010), the alternate Mediterranean diet score (aMED) and the Dietary Approaches to Stop Hypertension (DASH). Multivariable-adjusted means of biomarkers were compared across dietary index tertiles in the biomarker subcohort. The AHEI-2010, aMED (in men only) and DASH scores were related to a 10–20 % lower T2D risk, with the strongest associations in whites and the direction of the relationships mostly consistent across ethnic groups. Higher scores on the four indices were related to lower HOMA-IR, TAG and C-reactive protein concentrations, not related to leptin, and the DASH score was directly associated with adiponectin. The AHEI-2010 and DASH were directly related to HDL-cholesterol in women. Potential underlying biological mechanisms linking diet quality and T2D risk are an improved lipid profile and reduced systemic inflammation and, with regards to DASH alone, an improved adiponectin profile.